Silicon tunneling field-effect transistors with tunneling in line with the gate field - Fischer, Inga A.; Bakibillah, A. S. M.; Golve, Murali; Haehnel, Daniel; Isemann, Heike; Kottantharayil, Anil; Oehme, Michael; Schulze, Jörg (IEEE Electron Device Letters, 2013)
We present experimental results on the fabrication and characterization of vertical Si tunneling field-effect transistors (TFETs) in a device geometry with tunneling in line with the gate field. Compared to vertical Si TFETs without this geometry modification, on-currents are increased by more than one order of magnitude with ION =1.1μAμm at VDS = 0.5V and an IONIOFF ratio of 3.4 104 in n-channel operation. We present further suggestions for device improvements. © 1980-2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Semiconductor devices; transistors; tunneling; tunneling field-effect transistor (TFET)